Efficacy and Safety of Different Acupuncture Treatments for Cancer-Related Pain: A Systematic Review and Network Meta-Analysis - Tianle Xie MD; Can Liu MD; Yudi Wu MD; Xiuxiu Li MD; Qianyun Yang PhD; Jing Tan PhD (Integrative Cancer Therapies)
Background: Cancer pain is a prevalent and persistent issue, and while there have been some observations of the possible benefits of acupuncture in managing cancer pain, there is still debate regarding its safety and effectiveness. This study aims to compare the efficacy and safety of different acupuncture modalities in the treatment of cancer pain through a network meta-analysis. Methods: Between the time each database was created and June 3, 2024, eight databases were queried: PubMed, Cochrane, Embase, Web of Science, CNKI, Wanfang, VIP, and China Biomedicine. Randomized controlled trials investigating the use of various acupuncture and moxibustion techniques in the treatment of cancer pain were identified. Publication bias and quality of randomized controlled trials were assessed using the Cochrane Risk of Bias tool and the Jadad scale, and network meta-analyses were performed using Stata 15 and R 4.3.2. Results: We incorporated 111 studies encompassing 9549 individuals diagnosed with cancer, examining 29 distinct therapies. Network meta-analysis showed that, compared to Usual Medicine, Acupuncture + Usual Medicine + Traditional Chinese medicine (MD = −1.83, 95% CI: −2.86 to −0.80) could reduce NRS scores, Acupuncture + Traditional Chinese medicine (OR = 30.86, 95% CI: 3.75-254.20) could improve cancer pain relief, Moxibustion + Usual Medicine (MD = 2.12, 95% CI: 0.43-3.80) could effectively improve KPS score, Acupuncture + Application of Chinese medicine (OR = 0.16, 95% CI: 0.04-0.66) is associated with a lower incidence of constipation, Electro-Acupuncture + Usual Medicine (OR = 0.11, 95% CI: 0.03-0.45) shows a lower incidence of nausea and vomiting, Acupuncture + Moxibustion + Usual Medicine (OR = 0.29, 95% CI: 0.09-0.90) is associated with a lower incidence of dizziness. Conclusion: Acupuncture + Traditional Chinese medicine is the best intervention for different acupuncture methods in the treatment of cancer pain, and Moxibustion + Usual Medicine is the best intervention to improve the quality of life of patients.